الاقتصاد الأخضر وإمكانية تطبيقه في سورية والاستفادة منه في مرحلة إعادة الإعمار - ديوب محمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
ينطلق البحث من فكرة رئيسية هي أنَّ الاقتصاد الاخضر خيار استراتيجي لإعادة توجيه النموذج الاقتصادي نحو كل ما هو اخضر وبيئي والعمل على تعبئة الفاعلين والشباب لاستثمارهم بما يكفل انتاج ثروات جديدة ورفاه اقتصادي اكثر وإنصاف اجتماعي والتقليل من الفقر في ظل الاستثمار وإعادة فكرة الاقتصاد الاخضر والذي يوفر الكثير من فرص العمل للعاطلين, لاسيما أنَّه بات هدفاً استراتيجياً يستوجب من القطاعات العامة والخاصة والشركات التجارية دعمه ليكون حافزا للتنمية الاقتصادية والاجتماعية. The research starts from the main idea that the green economy is a strategic option to reorient the economic model towards all that is green and environmental and to mobilize the actors and young people to invest in them so as to produce new wealth, more economic welfare and social equity, reduce poverty under investment and re-idea the green economy Of employment opportunities for the unemployed, especially as it has become a strategic objective that requires public and private sectors and commercial companies to support it to be an incentive for economic and social development